Strategic Decision Speed and Firm Performance: Case Studies on the Indonesian Telecommunication and Professional Advisory Sectors - Tarigan, Samuel (Jurnal Telematika, 2009)
previous research has shown that strategic decision speed is positively correlated with firm performance especially in high velocity industry ((Wally and Baum, 2003; Eisenhardt, 1989). This posits further questions: What are the antecedents of strategic decision speed? How do those factors affect the decision process? How do different organizational contexts affect decision making? To answer the questions, two cases involving four companies in Indonesia were analysed using combined frameworks and organizational theories from Mintzberg (1996), Kreitner and Kinicki (2007) and Hart (1992). The data was collected through direct observations during the author’s consulting engagement in the four companies throughout a four-year period. Results show that organizational structure, culture, and power do have a significant influence on strategic decision making speed and performance. They also show that organizational contexts (Mintzberg, 1996) have implications on organizational structure, culture, and power. Further studies on the subject, involving Indonesian and other South East Asian companies could help managers improve the responsiveness of Indonesian companies to external changes in a globalized setting in the future and provide richer understanding on extant organizational theories.